2016
DOI: 10.1111/irv.12421
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral activity of aspirin against RNA viruses of the respiratory tract—an in vitro study

Abstract: AimAspirin (acetylsalicylic acid) has been used for more than 115 years in medicine. Research exists to show that aspirin has antiviral effects in vitro, for example, by blocking influenza virus propagation via NF‐κB inhibition when used at high concentrations and short‐term incubation steps. The aim of this study was to confirm the antiviral activity of aspirin against influenza virus and further elucidate the activity of aspirin against other respiratory viruses.MethodsTests to detect antiviral activity were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
63
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(68 citation statements)
references
References 32 publications
4
63
1
Order By: Relevance
“…Another study showed that ASA could reduce the pathogenic effects of HCV through the down-regulation of cellular oxidative stress and the enhancement of the expression and activity of Cu/Zn superoxide dismutase (SOD1) in infected cells [ 103 ]. Additionally, ASA showed a significant and dose-dependent antiviral activity against several other RNA viruses, including influenza A H1N1 virus, human rhinoviruses, and coxsackie virus subtype A9, this effect was observed with non-cytotoxic doses of ASA [ 19 ]. It is noteworthy that the beneficial effects of ASA against influenza virus infection have been in part attributed to ASA-mediated inhibition of PGE2 activity in macrophages and subsequent upregulation of interferon type I (IFN-1) production, leading to restricted viral replication and promoting T-cell-mediated immune response [ 104 ].…”
Section: Acetylsalicylic Acid As An Antiviral Drugmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study showed that ASA could reduce the pathogenic effects of HCV through the down-regulation of cellular oxidative stress and the enhancement of the expression and activity of Cu/Zn superoxide dismutase (SOD1) in infected cells [ 103 ]. Additionally, ASA showed a significant and dose-dependent antiviral activity against several other RNA viruses, including influenza A H1N1 virus, human rhinoviruses, and coxsackie virus subtype A9, this effect was observed with non-cytotoxic doses of ASA [ 19 ]. It is noteworthy that the beneficial effects of ASA against influenza virus infection have been in part attributed to ASA-mediated inhibition of PGE2 activity in macrophages and subsequent upregulation of interferon type I (IFN-1) production, leading to restricted viral replication and promoting T-cell-mediated immune response [ 104 ].…”
Section: Acetylsalicylic Acid As An Antiviral Drugmentioning
confidence: 99%
“…Additional mechanisms of ASA-induced effects include, among the others, modulation of nuclear factor kappa-light-chain-enhancer of activated B cells (NF‐κB) pathway, down-regulation of inducible nitric oxide synthase (iNOS), oxidative phosphorylation uncoupling, and increased permeability in mitochondria [ 17 ]. Along with its well-established role in reducing inflammation [ 16 ] and platelet aggregation [ 18 ], antiviral effects have also been proposed for ASA both against DNA and RNA viruses [ 19 ]. Among the latter effects, d , l -lysine acetylsalicylate (i.e., a lysine-salt formulation of ASA) reduced RNA synthesis and replication of the human CoV-229E and Middle East Respiratory Syndrome (MERS)-CoV titer in cultured infected cells [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Besides the wide usage of ASA in pain therapy, it was shown that ASA-mediated inhibition of the NF-κB-dependent induction of TRAIL and Fas/FasL, reduces influenza virus propagation [36][37][38]. ASA also displays anti-viral activity against cytomegalovirus [39] and human rhinoviruses [40].…”
Section: Introductionmentioning
confidence: 99%
“…Previously, SA dissolved in distilled water reported able to suppress zucchini yellow mosaic virus (ZYMV), cucumber mosaic virus (CMV), and tobacco mosaic virus (TMV) infection (Naylor et al, 1998;Radwan et al, 2007). SA dissolved in 70% ethanol showed a highly effective antiviral against the influenza virus (Glatthaar-Saalmüller et al, 2017). It is indicating that SA performance depends on the solvent type.…”
Section: Asmentioning
confidence: 99%